Sekty i związki wyznaniowe działające na terenie katowickiej części województwa śląsko-dąbrowskiego w latach 1945-1950 - Małachowska, Ewelina (Śląskie Studia Historyczno-Teologiczne, 2023)
After the Second World War the catholic church was the most numerous in Upper Silesia region but there were also few smaller churches and religion unions, which appeared in this area late XIX and beginning of XX century. We can mark the methodists, adventists and Jehovah’s Witnesses. Jehovah’s Witnesses’s activity was much more difficult after the year 1945. There were many reasons such as not clarified legal situation and disapproval of the authorities. However, the sects and religion unions developed in Upper Silesia what we can confirm through the growth of the numbers of members and increase of the numbers of buildings designed to the religious targets. The thesis explains the problem of sects and religion unions starting from the definitions and continuing through their activities noted by the national and ecclesiastic authorities.